A New Multi Criteria Decision Making-Sentiment Analysis Model to Evaluate Customer Focused Performance for Malaysian Food Service Industry - Shamsuddin, Jauriyah; Ramli, Razamin; Omar, Mohd Faizal (UUM, 2022)
Fast-food companies’ efforts to monitor their outlet performance in providing satisfactory food quality, service quality and price fairness have suffered due to the lack of effective decision support model. In order to develop more comprehensive and valuable insights into customer opinions and preferences for multiple fast-food outlets, this study utilize online reviews for evaluating customer satisfaction. The present study developed an integration model of sentiment analysis and multi attribute decision making method and identified the sub-criteria for food quality, service quality and price fairness via Term Frequency-Inverse Document Frequency analysis. To illustrate the efficacy and applicability of the proposed model, an empirical case study applying it to five McDonalds’ outlet namely Bukit Bintang, Bangsar, Titiwangsa, Taman Connaught and Technology Park Malaysia. The proposed approach is expected to be useful by fast food companies in monitoring the difference satisfaction level of the customer in their fast-food outlet by ranking their performance from the most to the least appropriate. Naturally, top rank fast-food outlet is suitable to be used as benchmark for others while improving customer experience for bottom ranked restaurant will contribute to the effort of maintaining the company’s positive brand image. Furthermore, the developed model can be employed to improve the efforts of local fast-food companies in terms of competitiveness and provision of systematic services.